THE IMPORTANCE MAINTENANCE BUDGETING FOR THE MOSQUES MANAGEMENT IN MALAYSIA: A SYSTEMATIC LITERATURE REVIEW - Wan Samsul Zamani Wan Hamdan; Mohamad Haszirul Mohd Hashim; Nor Amin Mohd Radzuan; Mohd Asrul Hassin; Rohil Amani Ismail, (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2024)
This article delves into the importance of effectively managing maintenance budgets in mosques across Malaysia. Mosques play a pivotal role in the country's cultural and religious landscape, and their proper maintenance is essential to ensure their functionality and longevity. The article identifies 15 critical factors that contribute to successful maintenance budget management in this context, encompassing financial control, fund management, documentation, functionality, strategic planning, program management, breakdown reduction, decision-making support, investment management, value for money, standardized operations, extended building life cycles, spare part management, and skill labour optimization. The purpose of this study is to provide mosque management authorities with a comprehensive framework for efficient maintenance budget management, which can ultimately enhance the overall upkeep and longevity of these important religious institutions. It covers the literature published on Emerald Insight between 2013 and 2023 and analyses the current state of knowledge about the importance of maintenance budgeting for the mosques management in Malaysia. The reviews using Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). However, it also acknowledges certain limitations, such as the need for further empirical research to validate these factors and their applicability across different mosque management scenarios. The originality of this work lies in its holistic perspective on maintenance budget management in Malaysian mosques, offering insights and recommendations that can be valuable for mosque administrators, government bodies, and researchers alike.